α/β-Globin mRNA ratio determination by multiplex quantitative real-time reverse transcription-polymerase chain reaction as an indicator of globin gene function - Chaisue, Chulaporn; Kitcharoen, Suttiphan; Wilairat, Prapon; Jetsrisuparb, Arunee; Fucharoen, Goonnapa; Fucharoen, Supan (Clinical biochemistry, 2007)
Imbalance in α/β-globin chains is an important determinant of thalassemia disease severity. This study examined the relationship between α/β-globin mRNA ratio and disease severity in various thalassemia genotypes. α- and β-globin mRNA contents of red blood cells of 75 α- and 32 β-thalassemia subjects (5 with β 0-thalassemia/Hb E) and 14 normal controls were measured using multiplex quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR). The α/β-globin mRNA ratio of each sample was calculated based on the 2 −ΔΔ C T method. A decrease of α/β-globin mRNA ratios in α-thalassemia subjects compared to normal controls correlated with the numbers of defective α-globin genes, whereas an increase of the ratios was observed in β-thalassemia. Subjects with β 0-thalassemia/Hb E disease had the highest α/β-globin mRNA ratio, followed by β 0-thalassemia trait and then β +-thalassemia trait, which correlated with decrease in severity of anemia. Coinheritance of α-thalassemia in β 0-thalassemia/Hb E resulted in a more balanced α/β-globin mRNA ratio and an amelioration of the anemia. This study indicates that imbalance in globin gene expression, the major factor affecting clinical severity of thalassemia, could be demonstrated by measuring α/β-globin mRNA ratio, which was conveniently and accurately determined by qRT-PCR. In α-thalassemia, α/β-globin mRNA ratio correlated with the number of functional α-globin genes present, whereas in β-thalassemia, the ratio provided a good indicator of disease severity.